유대교 구원론과 개신교 구원론 비교 연구 ‐ 아브라함 요수아 헤셸과 톰 라이트 중심으로 - 김윤정(KIM Yun-Jeong) (Changsin nondan, 2021)
이 글의 목적은 유대교 학자 아브라함 요수아 헤셸(Abraham J. Heschel)과 개신교 학자 톰 라이트(N. T. Wright)의 구원론을 비교하여 그것들의 공통점과 차이 점을 분석하는 것이다. 이 글의 중심 논지는 구원은 하나님의 선재적 은혜에서 출발하지만 인간의 후발적 순종으로 완성되며, 두 학자의 구원론이 상호 수렴한다는 것이다. 헤셸에 따르면 하나님의 이스라엘 구원은 이스라엘이 하나님과 언약을 맺음으로 시작한다. 헤셸은 인간의 모든 선행은 하나님과 함께 하는 행위이자 하나님으로부터 추동된 행위로서 인간이 토라와 미츠바를 준수할 때 이 땅에 정의와 공평이 가득 차게 되어 결과적으로 피조세계에 구원이 임하게 된다고 주장한 다. 헤셸은 율법을 지키는 행위 안에 율법을 지키는 힘이 있다고 단언하면서 성령의 견인을 지지하지 않으며, 하나님 백성 각각이 작은 메시아로서 세상 구원에 책임이 있다고 주장함으로써 메시아 주도의 구원론을 따르지 않는다. 한편 개신교 학자 톰 라이트(N. T. Wright)는 하나님은 창조의 하나님이자 언약의 하나님으로 잘못된 창조질서를 바로잡기 위해 이스라엘과 언약을 맺고, 언약 백성의 증표로 토라를 지킬 것을 명하셨다고 주장한다. 그에 따르면 토라(율법)의 본래 목적은 생명과 부활이었지만 이스라엘이 죄에 묶여 토라를 온전히 지키지 못하여 피조세계를 구원하는 일에 실패했다. 이에 하나님은 참 이스라엘의 대표자인 메시아 예수를 이 땅에 보내시고 그의 십자가 죽음과 부활을 통해 온 인류의 죄와 사망 문제를 해결하셔서 이방인까지 확대된 새로운 선민을 창조하신다(새 창조). 이제 새로운 선민(성도)은 그리스도 안에서 성령의 견인을 받아 옛 백성이 실패한 율법의 요구를 완성하게 된다(새 언약). 톰 라이트는 성도의 최종 구원은 그리스도가 재림하시는 날 행위대로 심판받아 결정되므로 이들의 율법 준수는 구원을 얻기 위한 필수 요소라고 주장한다. 이처럼 톰 라이트 역시 믿음이 결코 행위를 배제하지 않음을 인정한다. The present essay compares the soteriology of Abraham J. Heschel with that of N. T. Wright with focus on their commonality and dissimilarity. Its central thesis is that both approach each other in unfolding their respective understanding of God’s redemption of human beings. Heschel states that God’s redemption of Israel begins with her entry into the covenant with God at Sinai. Furthermore, he argues that the Torah itself is a driving force that enables Israel to keep the divine laws and one can encounter the Spirit of God in trying to keep the Torah. While not resorting to a theology of messianic mediation, Heschel emphasizes that each individual can contribute to redeeming the world by being a messianic individual. On the other hand, N. T. Wright unfolds a double perspective into the Torah. God has continued to make a saving covenant with human beings and the world by granting them the Torah whose original purpose was to bestow life and resurrection. However the Torah proved powerless to save human beings and became a complice with sin. But God eventually sent a messiah who would fulfill all the requirements of the Torah. The newly chosen people of Israel are enabled to fulfill the legal requirements of the Torah in union with the messiah Jesus through the Holy Spirit. The observance of the Torah by the new Israel is an essential prerequisite to her partake of the final salvation on the day of Jesus’ Second Coming. Overall, Tom Wright submits that faith in the N.T. does not necessarily nullify the faithful observance of the Torah. KCI Citation Count: 0